THE IMPACT OF SOCIAL MEDIA CRITICISM "JULID FISABILILLAH" AS A FORM OF SUPPORT FOR PALESTINE - M Imam Syaamil Nasution; Irfan al faris; Mochamad Slamet Riyadi; Muhammad Ikhsan Maulana (Jurnal Intelek Insan Cendikia, 2025)
The conflict between Israel and Palestine has been ongoing for over seven decades and involves many different factors, including Indonesia's role. This article uses a literature review to analyze the impact of the "Julid Fisabilillah" Movement on social media in supporting Palestine. The problem addressed is how this movement supports Palestine and how it affects social media dynamics. The research methodology includes primary data from books, journals, articles, and secondary data from official government news sites. The movement uses persuasive methods and trolling tactics, drawing on Digital Public Opinion theory, Digital Diplomacy, and Cyber Security concepts. While it has been successful in shaping public opinion, it is important to consider the risks of polarization and cybersecurity. In conclusion, the movement's success depends on a balanced and responsive approach and awareness of cybersecurity and digital diplomacy. In the era of digital information, it is crucial to maintain information authenticity and adapt to changes in social media dynamics to have a positive and lasting impact.